2009
DOI: 10.1111/j.1439-0523.2008.01591.x
|View full text |Cite
|
Sign up to set email alerts
|

A review on transgenic approaches to accelerate breeding of woody plants

Abstract: The long juvenile period of trees delays the breeding of new varieties. Flowering begins within 5-10 years in most cultivated forest trees under intensive management, but can take up to 40 years in some species and environmental conditions. To accelerate the breeding process several agrotechnical and biotechnical methods have been developed. Knowledge about genes controlling flower initiation in model plants like Arabidopsis thaliana, and identification of homologous genes in trees, have led to new possibiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 60 publications
1
80
1
2
Order By: Relevance
“…Occurrences of additional acrocona phenotypes, such as the intermediate shoot phenotypes that develop in the segregating plants during the fifth growth cycle, suggest that the acrocona trait is semidominant. In contrast, linkage analysis between genetic markers and the early cone-setting phenotype has previously suggested that early cone setting is a dominant monogenic trait (Acheré et al, 2004), while early cone setting in inbred acrocona mutants has been reported to occur with a much lower frequency (3%) than reported here (Flachowsky et al, 2009). This indicates that the accelerated growth conditions are of importance for the penetrance of the early cone-setting phenotype or that different variants of the acrocona mutant have been collected over the past 150 years.…”
Section: Discussioncontrasting
confidence: 42%
“…Occurrences of additional acrocona phenotypes, such as the intermediate shoot phenotypes that develop in the segregating plants during the fifth growth cycle, suggest that the acrocona trait is semidominant. In contrast, linkage analysis between genetic markers and the early cone-setting phenotype has previously suggested that early cone setting is a dominant monogenic trait (Acheré et al, 2004), while early cone setting in inbred acrocona mutants has been reported to occur with a much lower frequency (3%) than reported here (Flachowsky et al, 2009). This indicates that the accelerated growth conditions are of importance for the penetrance of the early cone-setting phenotype or that different variants of the acrocona mutant have been collected over the past 150 years.…”
Section: Discussioncontrasting
confidence: 42%
“…In citrus, the seedling juvenile period is considerably long (1.5 to 20 years), hampering classical breeding efforts, linkage analysis for various important traits and functional evaluations of genes of interest relating to reproductive organs. This is a common problem among woody plants, and various molecular approaches to shorten juvenile periods have been attempted (Flachowsky et al 2009). …”
Section: Fine Mapping Of a Locus Involved In Polyembryonymentioning
confidence: 99%
“…Linkage mapping from experimental populations is very widespread in herbaceous crops, such as wheat and rice, but this is not the case for tree crops, such as apple and pear . The main reasons are the high costs of maintaining a population of trees suitable for linkage mapping and their long juvenile period, especially when working with adult traits such as fruit quality or dormancy of reproductive buds (Flachowsky et al 2009;Grattapaglia and Kirst 2008;Neale and Kremer 2011;Myles 2013).…”
Section: Linkage Mapping Of Dormancy-related Traitsmentioning
confidence: 99%